2013
DOI: 10.1038/jhh.2013.50
|View full text |Cite
|
Sign up to set email alerts
|

Association of common variants in/near six genes (ATP2B1, CSK, MTHFR, CYP17A1, STK39 and FGF5) with blood pressure/hypertension risk in Chinese children

Abstract: Recent genome-wide association studies have identified several single-nucleotide polymorphisms (SNPs) that are associated with blood pressure (BP)/hypertension. In this study, we aimed to examine the established associations amongst Chinese children. We genotyped six SNPs (ATP2B1 rs17249754, CSK rs1378942, MTHFR rs1801133, CYP17A1 rs1004467, STK39 rs3754777 and FGF5 rs16998073) in Chinese children (N=3077, age range, 6-18 years). Based on the Chinese age- and sex-specific BP standards, 619 hypertensive cases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 36 publications
1
26
2
2
Order By: Relevance
“…These results are contrary to those obtained in Spain where the MTHFR TT genotype could predict the development of EH in males (Rodríguez-Esparragón et al, 2003). Our results confirm the fact that differences in ethnicity and geographical location could genetically predispose individuals to hypertension (Hong et al, 2010;Xi et al, 2014).…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…These results are contrary to those obtained in Spain where the MTHFR TT genotype could predict the development of EH in males (Rodríguez-Esparragón et al, 2003). Our results confirm the fact that differences in ethnicity and geographical location could genetically predispose individuals to hypertension (Hong et al, 2010;Xi et al, 2014).…”
Section: Discussioncontrasting
confidence: 70%
“…Further contrary results were found in a Japanese study that revealed that the risk of EH significantly increased in subjects with the 677CC genotype, whereas the C677T gene polymorphism contributed to lower blood pressure (Nakata et al, 1998). These controversial results have suggested that differences in ethnicity and geographical location could genetically predispose individuals to EH (Hong et al, 2010;Xi et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, the effect of minoxidil (Rogaine) on hair growth was also discovered as a side effect of patients taking this drug for hypertension (32,33). Common variants upstream of FGF5 have been implicated in three genome-wide association studies of blood pressure (3 × 10 −14 ≤ P ≤ 9 × 10 −25 ) (34-36) and replicated in independent cohorts (37,38). A mechanistic link between FGF5 variants associated with blood pressure and hair growth awaits further investigation.…”
Section: Discussionmentioning
confidence: 95%
“…Although the effects of ATP2B1 variants on systolic and diastolic blood pressure are small at around 1 mmHg (105), Levy et al (206) predicted the risk of developing hypertension to increase by 17 and 37% dependent on whether one or two respective alleles are affected. This finding of an association between ATP2B1 and hypertension is not just limited to adults as one study has determined that the ATP2B1 SNP rs2681472 is associated with an increased risk of hypertension in Chinese children (407), while the same SNP also predisposes Chinese women to early-onset preeclampsia during pregnancy (389). Using a gene-centric array in which~50,000 SNPs in 2,100 genes previously implicated in cardiovascular, metabolic, and inflammatory processes, Fontana et al (124) demonstrated a strong association between SNP rs12817819 in ATP2B1 and resistant hypertension, a condition in which raised blood pressure is not controlled despite the use of at least three antihypertensive drugs.…”
Section: A Pmca1 Hypertension and Cardiovascular Diseasementioning
confidence: 99%